Heavily Yb-doped phosphate large-mode area all-solid photonic crystal fiber operating at 990 nm. (12th June 2015) - Wang, Longfei; He, Dongbing; Feng, Suya; Yu, Chunlei; Hu, Lili; Qiu, Jianrong; Chen, Danping
Abstract: We demonstrate, for the first time to our knowledge, a 16 wt.% Yb-doped phosphate large-mode area all-solid photonic crystal fiber (AS-PCF) laser operating at 990 nm. By carefully tailoring the absorption and emission properties of the active glass and designing the structure of AS-PCF, the excitation of the 990 nm laser and the depression of the laser above 1  µ m can be easily realized even without any wavelength-selective optics. The single-mode behavior of PCF with a 35  µ m doped core, the largest core diameter of approximately 1  µ m in phosphate fiber, is theoretically investigated by finite-difference time-domain method and experimentally confirmed.